The framing effect in the serving style of volleyball players - Xie, G. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This paper studies the tendency of volleyball players to either avoid or pursue risks in serving. The findings will provide a theoretical and methodological guide for coaches to provide direction during a match.